Active site variants in STT3A cause a dominant type I congenital disorder of glycosylation with neuromusculoskeletal findings - Wilson, Matthew P.; Garanto, Alejandro; Pinto e Vairo, Filippo; Ng, Bobby G.; Ranatunga, Wasantha K.; Ventouratou, Marina; Baerenfaenger, Melissa; Huijben, Karin; Thiel, Christian; Ashikov, Angel; Keldermans, Liesbeth; Souche, Erika; et al. (The American journal of human genetics, 2021)
Congenital disorders of glycosylation (CDGs) form a group of rare diseases characterized by hypoglycosylation. We here report the identification of 16 individuals from nine families who have either inherited or de novo heterozygous missense variants in STT3A, leading to an autosomal-dominant CDG. STT3A encodes the catalytic subunit of the STT3A-containing oligosaccharyltransferase (OST) complex, essential for protein N-glycosylation. Affected individuals presented with variable skeletal anomalies, short stature, macrocephaly, and dysmorphic features; half had intellectual disability. Additional features included increased muscle tone and muscle cramps. Modeling of the variants in the 3D structure of the OST complex indicated that all variants are located in the catalytic site of STT3A, suggesting a direct mechanistic link to the transfer of oligosaccharides onto nascent glycoproteins. Indeed, expression of STT3A at mRNA and steady-state protein level in fibroblasts was normal, while glycosylation was abnormal. In S. cerevisiae, expression of STT3 containing variants homologous to those in affected individuals induced defective glycosylation of carboxypeptidase Y in a wild-type yeast strain and expression of the same mutants in the STT3 hypomorphic stt3-7 yeast strain worsened the already observed glycosylation defect. These data support a dominant pathomechanism underlying the glycosylation defect. Recessive mutations in STT3A have previously been described to lead to a CDG. We present here a dominant form of STT3A-CDG that, because of the presence of abnormal transferrin glycoforms, is unusual among dominant type I CDGs.